Preparation of Bioblends Using Spray Dryer and their Applications in Drug Delivery Systems - Ozsagiroglu, E.; Hayta, E.N.; Avcibasi Guvenilir, Y. (Asian Journal of Chemistry, 2015)
The importance of the study is to encapsulate L-ascorbic acid in biopolymers in order to obtain (i) enhancing its encapsulation efficiency (ii) increasing drug release ratio using different pH media. Microspheres based on polycaprolactone, polyethylene glycol and chitosan biopolymers are prepared by spray drying technique. Another importance of the study is the encapsulation of L-ascorbic acid which is an essential vitamin for humans. The study includes three different steps. First step is to obtain of low particle size, high surface area and homogeneous drug encapsulation material using spray dryer. Second part is determination of best efficient drug loading conditions. Final part of the study is about drug release experiments and calculation of drug release ratio in different pH media. At the end of studies, we achieved minimum 19.143 ± 0.023 μm particle size with 0.897 m2/g surface area, 99.13 % maximum drug loading and 93.18 % drug release ratio at 2.8 pH medium.